CATHODE RESTORATION OF SELONIUM ANIONS WITH THE FORMATION OF ITS POWDERS - Bayeshov A.B.,; Abduvaliyeva U.A.,; Bayeshova A.K.,; Zhubanys M., (Academic Scientific Journal of Chemistry, 2019)
The article shows the possibility of obtaining selenium powders by cathodic reduction of its anions in acidic and alkaline solutions. It has been established that in alkaline medium it is impossible to obtain selenium powders by reducing selenite ions. However, it is shown that selenium powders can be obtained by cathodic reduction of these ions in a sulfate medium.The main results of the conducted research are the production of selenium powders by cathodic reduction of “hardly recoverable”, and cathode “non-renewable” selenite-ions and determination of the regularities of this process. It has been shown for the first time that in sulfate solutions in the presence of titanium (IV) ions by cathodic reduction of selenite-ions, selenium powders can be obtained. The effect of the concentration of titanium (IV) ions, selenite-ions, and cathode current density on the formation of selenium powders was studied.It has been established that in the absence of titanium (IV) ions, selenium powders are not formed, and at their concentration equal to 5.0 g/l, the current yield for selenium powder formation reaches 70%. It has been proven that titanium (IV) ions have a catalytic effect on the cathode formation of selenium powders. It is shown that the formation of selenium powders proceeds in two stages, i.e. consists of an electrochemical and chemical reaction, namely, tetravalent titanium is reduced at the cathode to the trivalent state.It has been established that the titanium (III) ions formed in this case interact in the cathode space with selenium (VI) anions, reducing them to elemental selenium as an ultrafine powder. It is shown that an increase in the current density at the cathode leads to a decrease in the current efficiency for the formation of selenium powders. With an increase in the concentration of selenite-ions, the yield of selenium powders increases.It is established that with selenium (VI) concentration equal to 10.0 g/l, the yield of selenium powder formation is 68.1%, and at 30 g/l - 94.9%.The shapes and sizes of the obtained selenium powders were determined using an electron microscope.